2010
DOI: 10.2174/1876506801003010003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Pathophysiology of Intracranial Large Artery Stenosis

Abstract: Intracranial stenosis due to atherosclerosis is a disease of significant prevalence worldwide and is responsible for a significant economic burden due to stroke-related disability. Known risk factors including age, race, sex, and medical co-morbidities contribute to its incidence. While ischemic stroke and transient ischemic attack can develop from myriad mechanisms in patients with intracranial stenosis, it is likely that an interplay of hemodynamic failure, in-situ thrombosis, and distal embolism results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although malaria is endemic in Cameroon, there was no stroke related to malaria as David Celemerger et al have reported [9].…”
Section: Discussionmentioning
confidence: 96%
“…Although malaria is endemic in Cameroon, there was no stroke related to malaria as David Celemerger et al have reported [9].…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the impact of hypertension as a risk factor for intracranial atherosclerosis was already established from autopsy studies. Based on epidemiological studies, hypertension is associated with increased odds for the development of intracranial stenosis that ranged from 5 to 9.7 12 . Moreover, the risk further increased when hypertension was associated with other risk factors.…”
Section: Risk Factors For Strokementioning
confidence: 99%
“…Ischaemic heart disease was found in 34%, diabetes mellitus in 26%, dyslipidaemia in 30%, atrial fibrillation in 25%, carotid artery stenosis in 27% 11 . 15% patients were obese and family history of stroke was 12% 12 . They concluded that cerebral infarction accounts for 80 to 85% cases of stroke 8 .…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…Stroke due to intracranial atherosclerotic disease is caused by hemodynamic failure, in-situ thrombus from plaque disruption, and/or distal thromboembolism. 11 Secondary hypertension due to intracranial atherosclerotic disease is a common compensatory mechanism to maintain adequate cerebral perfusion.…”
Section: Rawal Et Almentioning
confidence: 99%